A technique for DNA cryptography based on dynamic mechanisms. (October 2019) - Biswas, Md. Rafiul; Alam, Kazi Md. Rokibul; Tamura, Shinsuke; Morimoto, Yasuhiko
Abstract: This paper proposes a technique for DNA cryptography based on dynamic mechanisms i.e . 'dynamic sequence table' and 'dynamic DNA encoding'. To form dynamic sequence table: initially, DNA base sequences are assigned to 256 ASCII characters randomly. Where to attain dynamism, positions of DNA base sequences are re-arranged iteratively following a mathematical series. Likewise, to form dynamic DNA encoding: the use of NCBI bank genome sequence with a mathematical series dynamically settles the number of DNA bases required to merge the ciphertext of every two chunks. Here, the way of encryption is: to transform the plaintext into DNA bases, to assign them w.r.t . ASCII characters using dynamic sequence table, to divide these data into a finite number of chunks, to encrypt them using an asymmetric cryptosystem, and lastly to merge the ciphertext of chunks through dynamic DNA encoding. Thus, the usage of dynamic mechanisms along with an asymmetric cryptosystem obviously enhances the secrecy level of data. Finally, the outcome of the proposed technique, a comparative study with existing techniques, the security analyses, and a statistical test according to the National Institute of Standards and Technology (NIST) to analyze the randomness of the generated ciphertext are presented.